1994
DOI: 10.1128/jb.176.8.2177-2183.1994
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, and disruption of a levanase gene of Bacillus polymyxa CF43

Abstract: The Bacillus polymyxa CF43 leLk gene, expressing both sucrose and fructan hydrolase activities, was isolated from a genomic library of B. polymyxa screened in Bacillus subtilis. The gene was detected as expressing sucrose hydrolase activity; B. subtilis transformants did not secrete the lelA gene product (LelA) into the extracellular medium. A 1.7-kb DNA fragment sufficient for le4 expression in Escherichia coli was sequenced. It contains a 548-codon open reading frame. The deduced amino acid sequence shows 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Several such frame shifts were described earlier in the sequences of family GH32: Bacillus subtilis sucrase (SwissProt accession number P07819), B. stearothermophilus levanase (P94469), Bacillus sp. L7 levanase (O31411), Debaryomyces occidentalis invertase (P24133), Aspergillus niger invertase (O13388), and Avena sativa invertase (Q43076) 25–30. To our knowledge, in two sequences frame shifts are found for the first time.…”
Section: Resultsmentioning
confidence: 82%
“…Several such frame shifts were described earlier in the sequences of family GH32: Bacillus subtilis sucrase (SwissProt accession number P07819), B. stearothermophilus levanase (P94469), Bacillus sp. L7 levanase (O31411), Debaryomyces occidentalis invertase (P24133), Aspergillus niger invertase (O13388), and Avena sativa invertase (Q43076) 25–30. To our knowledge, in two sequences frame shifts are found for the first time.…”
Section: Resultsmentioning
confidence: 82%
“…Most of the research has been performed on levansucrases, in particular on enzymes from Bacillus spp. (12,107,189,195) and Zymomonas spp. (71,187,219,220), and, to a lesser extent, Lactobacillus spp.…”
Section: Fructansucrasesmentioning
confidence: 99%
“…Reported and predicted subcellular localization showed that most plant FTases are vacuolar enzymes while sequences without a predicted signal peptide had a nuclear localizacion prediction (Supplementary Table 1). Fungi and bacteria FTases were extracellular enzymes, excepting some sequences for which an intracellular localization prediction was done (Supplementary Table 1), as reported previously (Bezzate et al, 1994;Ryan et al, 2005;Yuan et al, 2006).…”
Section: Single Amino Acids Responsible For Specific Characteristicsmentioning
confidence: 99%